NOVI PRAVCI U EU ELEKTRONSKOJ PRAVNOJ REGULATIVI POSLE 2015: PRAVNA REGULATIVA REMETILAČKE INOVACIJE - Savin, Andrej (Pravni zapisi, 2020)
This paper explores the gradual change of direction in the European digital policy on the content layer that took place after the introduction of the 2015 Digital Single Market Strategy. It argues that, while the main objectives of the pre-2015 policy have been the promotion and facilitation of the free movement of digital services through liberalisation, the post-2015 digital strategy changes direction to the defence against real and imagined threats and downplays the liberalising credo it was originally based on. The first part outlines the objectives of the EU digital policy pre-2015 and argues that low-key regulatory intervention in information society services and robust intermediary liability regime are its cornerstones. The second part explores the main regulatory methods post-2015: the emergence of platforms, new types of rules and new regulatory principles. The final section gives a critical overview and explains why the current approach is inadequate for the future.